If it's not what You are looking for type in the equation solver your own equation and let us solve it.
p-6=p-1+p-10
We move all terms to the left:
p-6-(p-1+p-10)=0
We add all the numbers together, and all the variables
p-(2p-11)-6=0
We get rid of parentheses
p-2p+11-6=0
We add all the numbers together, and all the variables
-1p+5=0
We move all terms containing p to the left, all other terms to the right
-p=-5
p=-5/-1
p=+5
| 25−6x=14+5x | | 4x+96=4x-24 | | 1.9s+6=3.1-6 | | 8=2r-5r | | ^x+2=11 | | 3x+-2(x+1)=-7 | | d/1.3=1.24 | | 3h-4=h+6 | | 13b-3b=20 | | 18p^2=12-15p | | 27=26p-1 | | -854t^2+64000t-150000=0 | | z÷11.4=6 | | 4=6r | | 5(x-3)+3=-12 | | 5x÷-x÷6=14 | | -854t^2+64000-150000=0 | | a+.93=1.42 | | 3(x+1)+2=x+9 | | 4-1/2a=6-a | | q^2+49q+144=0 | | -12=6(x+6)+6x | | q^2+49+144=0 | | 5(3x+6)=-14+29 | | 5x÷2-x÷6=14 | | 1/2x-3/4=2/3x+2 | | -79=-y–6y–16 | | 3(x+4)=4x+12-6 | | F(x)=3(2)^2-3(2)+1 | | 40+3x=180 | | 2/5x+1/6=3/10x+1/3 | | q^2-7q+144=0 |